Improved direct measurement of leptonic coupling asymmetries with polarized Z bosons. - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2001)
We present final measurements of the Z boson-lepton coupling asymmetry parameters A(e), A(mu), and A(tau) with the complete sample of polarized Z bosons collected by the SLD detector at the SLAC Linear Collider. From the left-right production and decay polar angle asymmetries in leptonic Z decays we measure A(e) = 0.1544+/-0.0060, A(mu) = 0.142+/-0.015, and A(tau) = 0.136+/-0.015. Combined with our left-right asymmetry measured from hadronic decays, we find A(e) = 0.1516+/-0.0021. Assuming lepton universality, we obtain a combined effective weak mixing angle of sin (2)theta(eff)(W) = 0.230 98+/-0.000 26.